Investigation of adoption behaviour for social commerce in the Kingdom of Saudi Arabia - Aldhahery, Muhammad; Wahiddin, Mohamed Ridza; Ahmed Khuhro, Mansoor; Ahmed Maher, Zulfikar (Institute of Electrical and Electronics Engineers Inc., 2019)
Social media fundamentally has changed the consumer's decision process. There are many research studies from different context for understanding the importance of social media, regrettably, not until recently, its business impact and opportunities were not seriously addressed. This is what led the Information System (IS) research community to come up with a new discipline known as Social Commerce (s-commerce). Hence an alternative means businesses through online social interactions emerge. This has made the social networking platform drives consumers to participate in social commerce. It is necessary to identify the significant factors that affect its acceptance. Thus, this research aimed to empirically examine the factors that affect s-commerce acceptance in Saudi Arabia. The quantitative research methodology was chosen to test the formulated hypothesis by subjective assessment of attitudes, opinions, and behavior of the people of Saudi Arabia.